PENGARUH STRES KERJA TERHADAP PRESTASI KERJA KARYAWAN DI BAGIAN SUMBER DAYA MANUSIA PADA PT. PETROKIMIA GRESIK - CITRA FARADIAN TONO (Jurnal Manajerial, 2018)
The aims of this study to investigate the effect of partially and simultaneously between work stress (physical symptoms, psychological symptoms and behavioral symptoms) to their job performance on the part of Human Resources at PT. Petrokimia Gresik. This research was done to the employees of PT. Petrokimia Gresik 89 employees that is as much a part of human resources as a sample. The sampling technique is Cluster Sampling. Data collection tool used in this study is a questionnaire. The data have been collected and processed using SPSS computing, prior to analysis by multiple linear regression techniques to test the classic assumption. Regression analysis showed that work stress (physical symptoms, psychological symptoms and behavioral symptoms) to their job performance at the Human Resources Management in PT. Petrokimia Gresik obtained by the equation: Y = 38.160 + 0.473 X1 + 0.231 X2 + 0.311 X3. The results showed that the three factors simultaneously affect the work performance of employees in the Human Resources Management in PT. Petrokimia Gresik is shown with a value of F test (4.365)> F Table (2.7). While partially obtained t value for X1 (physical symptoms) is 2.219; t value for X2 (psychological symptoms) was 2.109, and t value for X3 (behavior symptoms) are 2.134 bigger than t table (1.6628 ). From the evidence we can conclude that these three variables has an influence on employees' performance on the part of Human Resources at PT. Petrokimia Gresik. The amount of Adjusted R Square 10.3% was obtained, it is shown that work stress has a weak influence on employees' performance on the part of Human Resources at PT. Petrokimia Gresik.